Farmers perception and utilization status of improved forages grown in the natural resource areas of northwestern Ethiopia - MULUKEN SHIFERAW; BIMREW ASMARE; FIREW TEGEGNE; DESSALEGN MOLLA (Biodiversitas Journal of Biological Diversity, 2018)
Shiferaw M, Asmare B, Tegegne F, Molla D. 2018. Farmers perception and utilization status of improved forages grown in the natural resource areas of northwestern Ethiopia. Biodiversitas 19: 1568-1578. A study on the perception and utilization of improved forages grown in natural resource conservation areas was conducted in selected districts of northwestern Ethiopia. This study aims to investigate the perception of improved forage production and utilization system on natural resource conservation areas in selected areas of northwestern Ethiopia. Primary data was collected from selected households by interviewing using semi-structured questionnaire. Field observation and focus group discussion were also employed to enhance the survey data. A total of 180 households (90 from each district) were selected and interviewed. The collected data were analyzed with descriptive statistics using SPSS software version 20. The result indicated that the average land and livestock holding of respondents were 2.24 ha and 5.56 TLU per household, respectively. The most common forage production methods used by the smallholder farmers were broadcasting (41%), cutting (28%) and row seedling (18%) for both districts. For the majority of respondents (44%), the purpose of forage production of respondents was for animal fodder. Farmers in the study areas had a good perception about improved forage production as forages due have multifunction to the household in the form of soil conservation, fodder production, and income generation. Though improved forages have many roles in the livelihood and environmental management of the study districts, respondents had problems of skill in production and utilization of forages. This study elucidates that, relevant development and research interventions such as management and utilization of improved forage production should be the future direction of research and development. Sustainable forage development and use for nature conservation and is becoming very important to be a livestock feed source if cut and carry system is regularly applied.